A Crypt-Specific Core Microbiota Resides in the Mouse Colon - Thierry Pédron (American Society for Microbiology, 2012)
ABSTRACT In an attempt to explore the microbial content of functionally critical niches of the mouse gastrointestinal tract, we targeted molecular microbial diagnostics of the crypts that contain the intestinal stem cells, which account for epithelial regeneration. As current evidence indicates, the gut microbiota affects epithelial regeneration; bacteria that are likely to primarily participate in this essential step of the gut, microbiota cross talk, have been identified. We show in this article that only the cecal and colonic crypts harbor resident microbiota in the mouse and that regardless of the line and breeding origin of these mice, this bacterial population is unexpectedly dominated by aerobic genera. Interestingly, this microbiota resembles the restricted microbiota found in the midgut of invertebrates; thus, the presence of our so-called “crypt-specific core microbiota” (CSCM) in the mouse colon potentially reflects a coevolutionary process under selective conditions that can now be addressed. We suggest that CSCM could play both a protective and a homeostatic role within the colon. This article is setting the bases for such studies, particularly by providing a bona fide—and essentially cultivable—crypt microbiota of reference. IMPORTANCE Metagenomic typing of the whole-gut luminal microbiome was recently provided, revealing great opportunities for physiological and physiopathological analysis of the host-microbiota interface. On this basis, it appears increasingly important to analyze which niches of the gut exposed to a particular microbiota are of major functional importance, specifically focusing on the crypt, which accounts for permanent epithelial renewal, and to analyze how this microbiota compares to its luminal counterpart in composition and quantity. Crypt-specific core microbiotas may show themselves as important elements regarding crypt protection and homeostasis of its functions.